Consumers' perceptions in the valuation of food safety of vegetables in Davao City - Aban, Marjie L.; Concepcion, Sylvia B.
This paper analyzed the role of consumers' perceptions in the valuation of food safety of vegetables in Davao City using mediation framework, contingent valuation techniques and fishbein attitudinal model.This study selected ampalaya, pechay and lettuce for the valuation scenario since these vegetables were found to have harmful pesticides. Using household survey, the data was gathered in Davao City according to socio-economic status with a total number of 300 respondents. Results showed that majority of the consumers looked for fresh, clean and good-looking vegetables. The low income group usually buys vegetables in the wet market while the middle and high income groups buy vegetables from the wet market and supermarket and majority of them bought vegetables weekly. The consumers' definitions of food safety were safe to eat food, clean food, food with safety labels and chemical/pesticide-free vegetables. Minimal percentage from middle and high income groups were able to identify correctly the food safety labels while most of the low income group has not seen a food safety label itself. Most of these labels were organic and pesticide-free labels, Most of the respondents said that they were somewhat knowledgeable about the pesticide used in vegetables and they have very high safety concerns. Majority of them somewhat trust the food safety labels, but only a minimal number of respondents bought safety labeled vegetables since majority of the low income group were very sensitive to price when buying vegetables compared to middle and high income groups. Factors like years of schooling, low income group, high income group and number of media regularly used at home, were the significant determinants in predicting the WTP of food safety in vegetables through safety concerns. More than half of the respondents were willing to pay extra cost of food safety label in vegetables and majority of these respondents were from the middle and high income groups. They were willing to pay 10% to 15% higher than the conventional price.
Thesis, Undergraduate (BS Agribusiness Economics)--University of the Philippines, Mindanao
Keywords: Food industry and trade -- Davao City(Philippines) -- Safety measures; Vegetable trade -- Davao City(Philippines) -- Safety measures; Vegetable trade -- Davao City(Philippines) -- Safety measures -- Consumers' perceptions